2017
DOI: 10.1002/cam4.1144
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of Daxx NCR (Nuclear/Cytoplasmic Ratio) in gastric cancer

Abstract: In addition to regulating apoptosis via its interaction with the death domain of Fas receptor, death domain associated protein 6 (Daxx) is also known to be involved in transcriptional regulation, suggesting that the function of Daxx depends on its subcellular localization. In this study, we aimed to explore Daxx subcellular localization in gastric cancer (GC) cells and correlate the findings with clinical data in GC patients. Seventy pairs of tissue samples (GC and adjacent normal tissue) were analyzed immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 33 publications
(40 reference statements)
2
29
0
Order By: Relevance
“…In further studies of primary and metastatic tissues, they revealed that DAXX expression was higher in various cancer metastases than in the corresponding primary tumors 24 . Our previous studies 16 also indicated that increased DAXX NCR was associated with poor clinical outcomes in patients with GC. However, little research has been carried out on the relationship between the subcellular localization of DAXX and the clinical features of GC.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In further studies of primary and metastatic tissues, they revealed that DAXX expression was higher in various cancer metastases than in the corresponding primary tumors 24 . Our previous studies 16 also indicated that increased DAXX NCR was associated with poor clinical outcomes in patients with GC. However, little research has been carried out on the relationship between the subcellular localization of DAXX and the clinical features of GC.…”
Section: Discussionmentioning
confidence: 81%
“…Emerging evidence has suggested that DAXX is a key oncogene in tumorigenesis. Our previous study found that patients with GC often display a higher DAXX NCR 16 ; however, the underlying mechanisms of DAXX remains unknown. In this study, for the first time, we demonstrated that cDAXX and nDAXX expression have opposite effects on the survival prognosis of patients with GC.…”
Section: Discussionmentioning
confidence: 92%
“…The study was approved by the Review Board of the Second Affiliated Hospital of Wenzhou Medical University. The tissue microarray (TMA) was constructed as described previously 20 . All the patients were aware of the research and signed the informed consent form.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry on a tissue microarray, constructed as described previously, 20 was performed for the detection of CD2AP expression. In brief, the sections were dewaxed by incubation with dimethyl benzene at 45°C for 60 minutes and then immersed in distilled water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation